Pengaruh Minat, Kreativitas Dan Gaya Belajar Terhadap Hasil Belajar Matematika Pada Siswa Kelas 5 Sekolah Victory Plus Bekasi - Wahyu Nofiyanti; Sinambela, Lijan P.; Yusriani Sapta Dewi (Jurnal Satya Mandiri Manajemen dan Bisnis, 2019)
This riset aims to prove the influence of interest, creativity and learning styles towards mathematics learning outcomes. The data collection is done using questionnaires. Based on the results of the study it was concluded that: (1) There is a significant effect of interest in mathematics learning result; (2) There is a significant effect of creativity in mathematics learning result (3) There is a significant effect of learning styles in mathematics learning result and (4) There is a significant effect of interest, creativity and learning styles together in mathematics learning result.